Answer:
C. -1 is less than x
Step-by-step explanation:
-3 < 4x + 1
-3-1 < 4x +(1 -1)
-4 < 4x
-4/4 < 4x/4
-1 < x
Answer:
50
Step-by-step explanation:
answer is 50
Answer:
Spencer and Abigail are correct
Lauren is incorrect
Step-by-step explanation:
Spencer and Abigail are correct
Slope = change in y ÷ change in x
Or ![m=\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Let
= (3, -1)
Let
= (5, 4)
![\implies m=\dfrac{4-(-1)}{5-3}=\dfrac52](https://tex.z-dn.net/?f=%5Cimplies%20m%3D%5Cdfrac%7B4-%28-1%29%7D%7B5-3%7D%3D%5Cdfrac52)
This is Spencer's method
Let
= (5, 4)
Let
= (3, -1)
![\implies m=\dfrac{-1-4}{3-5}=\dfrac52](https://tex.z-dn.net/?f=%5Cimplies%20m%3D%5Cdfrac%7B-1-4%7D%7B3-5%7D%3D%5Cdfrac52)
This is Abigail's method
It doesn't matter which point you label as point 1 and point 2, as long as you carry out the slope calculation correctly.
Lauren's calculation is wrong as she calculated her slope as:
where it should have been ![m=\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)